Integrasi Kecerdasan Buatan Dalam Pengembangan Sumber Daya Manusia Sebagai Tantangan Dan Peluang Di Era Digital - sulistiarini, irna; Isa Anshori, Mochammad (Cattleya Darmaya Fortuna, 2025)
The integration of AI shows its potential in improving the efficiency and effectiveness of human resource development. This study aims to identify how artificial intelligence (AI) can be integrated into human resource development, as well as opportunities to optimize its benefits while addressing existing challenges. Data were obtained from several sources including academic databases, scientific journals, books, research and other sources of information related to the research theme. The results of the study concluded that the integration of artificial intelligence (AI) in human resource development (HRD) improves recruitment and training efficiency, but also presents ethical and privacy challenges. Organizations need to adopt new technologies while creating an inclusive work environment to increase competitiveness and sustainability.